Hubungan Perilaku Caring Perawat dengan Tingkat Kepuasan Pasien di Poli VCT RSUD Gambiran Kota Kediri Berdasarkan Teori Watson - Titik Juwariah; Nanang Bagus Witjayanto Joyo; Winanda Rizki Bagus Santosa (Journal of Ners and Midwifery, 2014)
Caring can be seen through the attitude and action that are characteristic of the behavior. As the health care service, caring so important for patient. Patient satisfaction is indicator of quality insurance of hospital. The purpose of this study was to analyze the relationship of caring behavior of nurse with patient satisfaction in VCT clinic Gambiran hospital with Watson theory approach. Methode: Research study was analytic corelational design. Research samples was 50 of patient at VCT clinic Gambiran hospital. Data collected at July to September 2014 by using questionnaire and proceeded by Spearman Rho test. The result of this study was that caring behavior nurse correlated with patient satisfaction with p-value=0,000. According the result of this study are expected to be the input for hospitals to improve quality of service by apply minimum standart service that are caring behavior.